A Time-motion Comparison of Itemized Treatment Costs in First and Second In Vitro Fertilization Attempts: A United Kingdom Fertility Centre Experience - Christopher A. Jones; Olivia J. Carpinello; Dev Kumar; Louis G. Keith; Renju S. Raj; E. Scott Sills (Journal of Health Economics and Outcomes Research, 2013)
# Objective To assess the difference in cost between initial and second in vitro fertilization (IVF) cycles in the United Kingdom.